Self Medication Practices Among Urban Slum Dwellers In South Indian City - Dr.PAVAN KUMAR KULKARNI,; Dr.MASEER KHAN,; Dr.A.CHANDRASEKHAR, (International Journal of Pharma and Bio Sciences, 2012)
In developing countries like India most episodes of illnesses are treated by self-medication because of easy availability of a wide range of drugs commercially. Inadequate health services results in increased proportions of drugs used as self-medication compared to prescribed drug A cross-sectional study comprising 118 households was carried out in an urban slum community to know the knowledge, awareness and perception of self-medication practices by house to house survey. Self-Medication was practiced by 30.5% of respondents and was more prevalent among 26-35 age group. Allopathic drugs were commonest mode of self-medication (77.7%). The commonest reason for self medication was high cost of consultation of private doctors (61.1%). Majority of the study population(90%) respondent that they don’t know the type of drugs given by the pharmacist. When asked about antibiotic usage 96% of study population replied their ignorance.